Effects, tolerance mechanism and mitigation approaches of salt stress in Maize (Zea mays L.): A review - Nasreen, Saima; Mehmood, Khalid; Mahmood, Imran; Irfan, Muhammad; Ali, Habib; Yaseen, Esha (Journal of Pure and Applied Agriculture, 2023)
Salinity is one of the major abiotic stresses for crop productivity across the globe. Soil salinity has a dual impact on plants: osmotic and ionic effect. Maize is the third most important cereal crop of the world that is helping out to meet the food requirements of the world. Higher osmotic stress and ionic toxicity cause oxidative stress as well as nutritional imbalances in maize that has effects on germination rate, plant height, root growth, biomass yield, pollen grain viability and yield of maize crop. In response to salinity, maize have evolved resistance mechanisms including ionic balance maintenance, osmoregulation, stomatal conductance regulation and phytohormonal regulation. The ionic balance is maintained by increasing the K+ ions and decreasing Na+ in cytosol. The osmoregulation takes place by increasing inorganic and organic compounds. The stomatal conductance regulated by production of abscisic acid. The production of jasmonate, ABA, oxidative enzymes, spermidine and polyamine are also involved to tolerate salt stress. This stress is also being mitigated by using approaches such as soil reclamation, seed priming, exogenous application of plant growth regulators and molecular & genetic breeding techniques. The present review highlights the impact of salt stress on morphological, physiological and biochemical responses, resistance mechanisms of maize and various approaches to mitigate the effects of salt stress for its improved productivity. © 2021 Department of Agricultural Sciences, AIOU